An Ecofeminist Analysis of Fartuma Kusow’s Tale of A Boon’s Wife - Nigus Michael Gebreyohannes; Abiye Daniel Ambachew (HUMANISMA : Journal of Gender Studies, 2022)
This article examines the exploitation of women, nature, and certain other oppressed groups in Fartumo Kusow’s novel, Tale of a Boon’s Wifeusing an ecofeminist literary approach.The novel tackles a number of contemporary Somalia-related concerns. It addresses topics including sociocultural factors, the strongly ingrained patriarchal system, the effects of war and violence, the issues associated with environmental disasters, etc. Thus, exploring this novel from an ecofeminism perspective will show how the writer addressed gender injustice, environmental crises, and various types of dominance and exploitation rooted in their societies. To extract relevant data from the novel, a close reading was done. Then, a textual analysis was employed to analyze the extracted texts. Therefore, based on the analysis made, the novel significantly portrays the deep-rooted patriarchal system in Somalia. Women and girls are especially vulnerable to both domestic and public abuse. The novel also demonstrates that continued war and conflict, and drought have a direct and indirect impact on women, children, farmers, animals, and the natural environment. It also shows that war and instability create a good situation for those military officials and members to subjugate women and control vast amounts of fertile land for their own personal gain by displacing poor farmers. Furthermore, the novel has portrayed discrimination based on clan and class differences in its impact on women and other subordinate groups. On the other hand, it portrays Idil, the main character, resisting all these differences and giving value to all humans, animals, and the natural environment, including the land. Finally, the author has put all these unprivileged groups together: women, children, animals, farmers, and the natural environment, including the land, in one category to show how they are mistreated and exploited simultaneously by powerful men.